2017
DOI: 10.1111/mec.14070
|View full text |Cite
|
Sign up to set email alerts
|

Differential sharing and distinct co‐occurrence networks among spatially close bacterial microbiota of bark, mosses and lichens‬‬

Abstract: Knowledge of bacterial community host-specificity has increased greatly in recent years. However, the intermicrobiome relationships of unrelated but spatially close organisms remain little understood. Trunks of trees covered by epiphytes represent complex habitats with a mosaic of ecological niches. In this context, we investigated the structure, diversity and interactions of microbiota associated with lichens, mosses and the bare tree bark. Comparative analysis revealed significant differences in the habitat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 63 publications
(120 reference statements)
7
53
2
Order By: Relevance
“…In our present study, co-occurrence networks in melt ponds and periglacial rivers suggested that most of the involved nodes belonged to the rare sub-communities. This pattern has previously been reported from other glacial environments in Tibet Plateau [23] and from other habitats, such as soil [58,59], rivers [60], and oceans [61]. Moreover, the over-proportional roles of rare taxa were also shown by our finding that all 7 keystones in melt ponds and 11 out of 12 keystones in periglacial rivers were affiliated with rare OTUs.…”
Section: The Role Of Rare Sub-communities On the Bacterial Communitiesupporting
confidence: 89%
“…In our present study, co-occurrence networks in melt ponds and periglacial rivers suggested that most of the involved nodes belonged to the rare sub-communities. This pattern has previously been reported from other glacial environments in Tibet Plateau [23] and from other habitats, such as soil [58,59], rivers [60], and oceans [61]. Moreover, the over-proportional roles of rare taxa were also shown by our finding that all 7 keystones in melt ponds and 11 out of 12 keystones in periglacial rivers were affiliated with rare OTUs.…”
Section: The Role Of Rare Sub-communities On the Bacterial Communitiesupporting
confidence: 89%
“…5), thus indicating the potential for widespread cooperative and syntrophic relationships between most fungal members, or multiple trophic levels, as well as the potential for sharing niches based on nutritional preference and functional distinctiveness in the phyllosphere micro-environment. This overwhelmingly positive association has also been reported in microbial networks associated with mosses, lichens and the bark of maple trees 29 , and in the rhizosphere zone of wild oat 115 .…”
Section: Discussionsupporting
confidence: 57%
“…Further, exploration may uncover possible keystone taxa that exert a considerable impact on community structure and function, regardless of their abundance 20,21 . Co-occurrence network analysis based on high-throughput sequencing data has been increasingly applied to examine the ecological interactions among microorganisms in different habitats including water environments [22][23][24] , human and animal digestive tracts 25,26 , soil 27,28 , and tree trunks 29 . Nevertheless, compared to bacterial communities, far fewer studies have been conducted to investigate co-occurrence patterns of fungal microbiome especially in plant associated communities.…”
mentioning
confidence: 99%
“…The available datasets were utilized for complementing analyses of the lichen microbiome [4, 28]. All datasets employed in this study were obtained with L. pulmonaria samples from the same sampling site.…”
Section: Methodsmentioning
confidence: 99%
“…Only recently, Aschenbrenner et al [3] reported about the presence of Spartobacteria ( Verrucomicrobia ) in lichens, a poorly investigated group earlier found to be abundant in soil and aquatic environments [9, 37, 71]. New data reinforced the hypothesis that specific members of Chthoniobacterales ( Spartobacteria ) and Sphingobacteriales ( Bacteroidetes ) could potentially be more important colonizers of L. pulmonaria [4]. A major obstacle in studying the as yet uncultivable Chthoniobacteria was their absence in former releases of public sequence databases due to their rather low occurrence in terrestrial habitats and thus low presence in most environmental samples.…”
Section: Introductionmentioning
confidence: 99%